INTERSECTING OPPRESSION OF GENDER AND RACE IN TONI MORRISON’S THE BLUEST EYE AND GOD HELP THE CHILD - Nurhayati, Ari (LITERA, 2019)
White domination in America can make white ideology of beauty spread and influence the African-American society. Toni Morrison’s novels, The Bluest Eye and God Help the Child, depict the influence. This study attemps to uncover the intersecting oppression of race and gender in the novels and to explain how African-American women cope with the oppression. This study is descriptive qualitative research. The data sources are Morrison’s novels The Bluest Eyeand God Help the Child. The study has two findings. Firstly, African-American society experiences oppression as an impact of the white beauty hegemony. The most disadvantageous oppression is the internalization of white beauty values. Holding such values makes African-American women feel inferior and hate their own physical characteristics that are far from the white ideal of beauty. Meanwhile, African-American women who have darker skin colors experience the hardest oppression because they also become the victims of oppression committed by some circles of African-American society, which tend to consider them unequal. It reflects the complexity of oppression experienced by African-American women. Secondly,self-consciousness is the main factor of attempts to release them from the oppression. Without self-consciousness, African-American women can be trapped in values that deteriorate their self-pride of identity. Keywords: intersecting oppression, African-American women, skin color